Sex and eroticism in Mesopotamian literature - Leick, Gwendolyn, 1951- (Routledge, 1994)
A fascinating book shedding light on the sexual culture of one of the earliest literate civilisations and provides a new contribution to current debates about sex, eroticism and gender.